2002
DOI: 10.1063/1.1503160
|View full text |Cite
|
Sign up to set email alerts
|

Rapid thermal annealing effects on blue luminescence of As-implanted GaN

Abstract: Rapid thermal annealing effects on blue luminescence of As-implanted GaN grown by metalorganic vapor phases epitaxy were investigated by means of photoluminescence and photoluminescence excitation measurements. The locations of the As-implantation induced bands and the associated transition channels for the emission were determined to characterize the As-implanted GaN. After the rapid thermal annealing treatment, the deep As-related levels become more ready to be populated by photoexcitation at low temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Silver replaces a copper cofactor required by the receptors for binding ethylene, resulting in ethylene insensitivity (11). The etr2-1 and the etr1-1 mutants are both missense mutations within the predicted ethylene-binding regions of the receptors that result in dominant ethylene insensitivity (17,33). Treatment of ctr1 plants with silver or introduction of either the etr2-1 or the etr1-1 mutations into the ctr1 background abolished ethyleneinduced turnover of ETR2 protein (Fig.…”
Section: Ethylene Perception By the Receptors Initiates Ligand-inducedmentioning
confidence: 99%
“…Silver replaces a copper cofactor required by the receptors for binding ethylene, resulting in ethylene insensitivity (11). The etr2-1 and the etr1-1 mutants are both missense mutations within the predicted ethylene-binding regions of the receptors that result in dominant ethylene insensitivity (17,33). Treatment of ctr1 plants with silver or introduction of either the etr2-1 or the etr1-1 mutations into the ctr1 background abolished ethyleneinduced turnover of ETR2 protein (Fig.…”
Section: Ethylene Perception By the Receptors Initiates Ligand-inducedmentioning
confidence: 99%
“…In the case of GaN, the doping with As has been studied with respect to its luminescence behaviour [15][16][17][18][19][20][21][22] and, at higher concentrations, with regards to the formation of GaAs x N 1−x alloys and the related modification of the GaN band gap [17,21,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, while, on the As-rich side of the phase diagram, it is possible to incorporate up to ~10-15% of N into cubic GaAs [3,4], on the N-rich side not more than ~1% of As in GaN have been achieved [5][6][7][8]. In the intermediate region, usually the coexistence of hexagonal N-rich GaAsN and cubic As-rich GaNAs phases is observed.GaN which is lightly As-doped is also highly interesting due to the fact that it shows intense blue luminescence centered around 2.6 eV, as observed already many years ago in Asimplanted GaN by Pankove and Hutchby [9] and Metcalfe et al [10], and subsequently also found in GaN doped with As during growth [5,[11][12][13][14][15][16]. The chemical nature of the 2.6 eV blue luminescence and the fact that it results from optical centers involving one As atom only was unambiguously proven by means of the radiotracer photoluminescence (PL) work of Stötzler et al [17], who studied the luminescence along the radioactive decay chains 71 As→ 71 Ge→ 71 Ga and 72 Se→ 72 As→ 72 Ge.…”
mentioning
confidence: 72%
“…GaN which is lightly As-doped is also highly interesting due to the fact that it shows intense blue luminescence centered around 2.6 eV, as observed already many years ago in Asimplanted GaN by Pankove and Hutchby [9] and Metcalfe et al [10], and subsequently also found in GaN doped with As during growth [5,[11][12][13][14][15][16]. The chemical nature of the 2.6 eV blue luminescence and the fact that it results from optical centers involving one As atom only was unambiguously proven by means of the radiotracer photoluminescence (PL) work of Stötzler et al [17], who studied the luminescence along the radioactive decay chains 71 As→ 71 Ge→ 71 Ga and 72 Se→ 72 As→ 72 Ge.…”
mentioning
confidence: 72%
See 1 more Smart Citation